India and the romantic imagination - Drew, John 1939- (New Delhi ; New York : Oxford University Press, 1987)
Study on the influence of India on English romantic poetry.
Includes bibliographies and index.
Keywords: English literature -- Indic influences; Romanticism -- Great Britain; English poetry -- 19th century -- History and criticism; Anglo-Indian literature -- History and criticism; British -- India -- Intellectual life; India -- In literature